The Modular vs. the traditional approach a pilot study in the teaching of community health nursing - Abarquez, Lupe F.
This project is an attempt at innovation using the modular approach in the teaching of community health nursing. The aim is to ascertain how the concept may be adopted throughout the course. A pilot study was undertaken for a specific portion of the course using a randomized cross-over design. The study group, composed of 39 third year nursing students, was divided into two and each group was alternately exposed to the traditional and modular approach in the teaching of Demography and Biostatistics. The effectiveness of the module as compared to the lecture was determined by 1) the extent to which the objectives were achieved which was obtained by a gain score comparison of the pre and post tests and 2) the students' perceptions of the effectiveness of the method as a whole as well as of its different parts, which were obtained by means of a questionnaire. Acceptability of the method was measured by 1) the extent to which it fitted with the learning style of the student, 2) the extent to which it was recommended in the course and 3) the students' perceptions of the advantages of the method, all of which were obtained by means of the questionnaire. Efficiency of the method was measured in terms of user time and the time/cost of development of the module or preparation for the lecture. Results of the study showed no significant differences in the mean gain score of the module and lecture groups in both subject matters. Based on this and the responses to the questionnaire, it can be concluded that the modular approach is an equally effective, acceptable and efficient alternative to the traditional one. What is important is not for the teacher to select from among the two methods but to: 1) suit the individual needs of the students by providing them a choice of at least two methods. 2) utilize to the fullest the features that have been proven to make the method effective; 3) make the necessary modifications to adapt to the learners' characteristics and needs. In view of the learning that takes place and the planning that goes into the development of modules, one might as well develop modules for a well-planned instructional design.